The changing research context: implications for leadership - Billot, J. (Taylor and Francis, 2011)
Within the changing tertiary environment, research activity and performance are coming under greater pressure and scrutiny. External policy and funding directives are resulting in revised institutional objectives, requiring variations to organisational structures and processes. These changes have an impact on the relationship between the institution and the individual. Institutional executives provide benchmarks for revised activity and performance, while academic staff respond to new internal directives and accountability requirements by reprioritising their responsibilities. At the same time, there will inevitably be an informal evaluation of the resourcing and support provided for staff as they experience the institutional push to attain greater research outputs. Within this dynamic environment there is the potential for tensions and negative outcomes if interactions are not carefully directed. The implications for leadership are obvious. What is less evident is whether the strategic intent of the institution resonates through the institution in alignment with the development of a supportive research culture.
Keywords: Higher education research; Leadership; Research culture; Research funding